H19 is involved in the regulation of inflammatory responses in acute gouty arthritis by targeting miR-22-3p - Xue, Yan-Yan; Liu, Hui-Jie; Sun, Zhan-Juan; Xiang, Ting; Shao, Ping (Immunologic research, 2022)
A great number of studies have confirmed that long noncoding RNA (lncRNA) are involved in the regulation of inflammatory response in acute gouty arthritis (AGA). This paper aimed to survey the regulatory mechanism of H19 on AGA. The expression of serum H19 in all subjects was examined by qRT-PCR. The ROC curve was used to estimate the diagnostic value of H19 for AGA. THP-1 cells were induced by MSU to establish in vitro AGA cell model. The concentrations of cytokines such as IL-1β, IL-8, and TNF-α were tested by ELISA. Luciferase reporter gene analysis was used to verify the interaction between H19 and the 3′-UTR of miR-22-3p. Expressions of serum H19 in AGA patients were significantly higher than that in controls. The ROC curve indicated the potential of H19 as a diagnostic marker for AGA. Cell experiments revealed that the downregulation of H19 significantly inhibited the expressions of IL-1β, IL-8, and TNF-α. The luciferase reporter gene assay manifested that miR-22-3p is the target gene of H19. And knockdown of miR-22-3p overturned the downregulation of inflammatory factors caused by H19 inhibition. H19 aggravated MSU-induced THP-1 inflammation by negatively targeting miR-22-3p, suggesting a new regulatory mechanism and potential therapeutic target for AGA.